Transit and Bikeshare Connectivity in Detroit: New Insights on Socioeconomic and Infrastructure Factors Impacting Perceived Quality of Service - Anahita Zahertar; Steven Lavrenz (Journal of Urban Mobility)
Active transportation systems are critical to equitable urban mobility, particularly in Detroit, where access to jobs, education, and healthcare remain uneven. This study evaluates user satisfaction with transit and bikeshare coverage across the Detroit Metropolitan Area through a survey of 1042 individuals, with 333 responses retained for analysis. Using fixed and random parameter ordered probit models, we find that lower-income and female respondents are significantly more likely to report inadequate service coverage. Perceived unfamiliarity with routes or station locations, as well as longer travel times, also contribute to dissatisfaction. Random parameter models reveal substantial heterogeneity in responses, underscoring the need for more nuanced, equity-focused planning. These findings offer data-driven insights to guide future investments in multimodal connectivity and active transportation infrastructure.